2012
DOI: 10.4103/0975-9476.100168
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory study to evaluate tolerability, safety, and activity of Ashwagandha (Withania somnifera) in healthy volunteers

Abstract: Ashwagandha (Withania somnifera) (WS), a “rasayana” drug, is recommended for balavardhan and mamsavardhan. The study was intended to evaluate dose-related tolerability, safety, and activity of WS formulation in normal individuals. The design was prospective, open-labeled, variable doses in volunteers. Eighteen apparently healthy volunteers (12M:6F, age:18-30 years, and BMI: 19-30) were enrolled. After baseline investigations, they received WS capsules (Rx) (aqueous extract, 8:1) daily in two divided doses with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 7 publications
3
76
0
2
Order By: Relevance
“…This finding is congruent with reports in the literature showing a general lack of toxicity with treatment by similar or same formulations of winter cherry tree extracts [11, 3941] in humans. The research results, in aggregate, strengthens the validity in utilizing a natural plant extract such as AshwaMAX to treat gliomas.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is congruent with reports in the literature showing a general lack of toxicity with treatment by similar or same formulations of winter cherry tree extracts [11, 3941] in humans. The research results, in aggregate, strengthens the validity in utilizing a natural plant extract such as AshwaMAX to treat gliomas.…”
Section: Discussionsupporting
confidence: 92%
“…However, withanolides are effective against different cell culture strains of cancers [35] as well as in numerous preclinical models of murine and human cancer xenografts [36], including human GBM [11]. Such investigations have also included toxicity studies in preclinical models[37, 38] and in clinical subjects [39, 40]. In general, these studies showed good tolerability to oral doses of either purified Withaferin A or Withania extracts that contain withanolides with minimal side effects Future preclinical and clinical investigations should include investigating the impact of metabolism on efficacy of Withaferin A [35].…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion that WS is a safe herbal supplement for general use agrees with findings from a recent evaluation of the tolerability and safety of WS in human participants. 21 Additional research is needed to determine standardization of WS supplements and dosage recommendations.…”
Section: Discussionmentioning
confidence: 99%